Service-learning pedagogy in teacher education: an examination of individual and group experiences - Tietjen, Laura L. (Kansas State University, 2016)
There is a call for education, including teacher education, to transform from solely transmitting knowledge to creating dynamic learning opportunities for students to experience real-world situations so they can develop the skills and competencies necessary to navigate a changing and unpredictable world. Service-learning is proposed as one strategy to facilitate this transformation. Therefore, the purpose of this qualitative case study was to describe how individual or group service-learning experiences might impact the attitudes and beliefs of pre-service teachers in a teacher education course. This study was guided by two research questions: How do pre-service teacher participants describe their individual or group service-learning experiences within the context of a required teacher education course? In what ways do participants' attitudes and beliefs towards service-learning vary, based on individual or group service-learning experiences? The service-learning experiences for this study were designed using experiential educational theory and a blended framework from service-learning common goals (academic enhancement, personal/professional growth, and civic learning) and common components (academic material, critical reflection and relevant service) (Ash, Clayton, & Moses, 2009). Fourteen pre-service students agreed to participate in the study. Two sources of data were identified, (a) individual semi-structured, face-to-face interviews and (b) critical reflective journals written by participants. Findings suggest that service-learning experiences reinforce academic content including experiential education. Personal and professional growth and an understanding of diversity can result from service-learning experiences. Teacher involvement in the local community was viewed by participants as important for student-teacher relationships and to improve connections between the school and the community. Participants of the study viewed critical reflection as a fundamental component in service-learning. Self-identified personality type can impact how each participant described their individual or group service-learning experiences, including benefits of social interaction and collaboration. Individual and group service-learning present different challenges in implementing effective experiences. Participants’ beliefs and attitudes did not vary based upon individual or group service-learning experiences. In conclusion, incorporating the experiential pedagogy of service-learning in teacher education programs can better prepare pre-service teachers for the very unpredictable nature of teaching.
Keywords: Service-learning; Teacher education; Experiential education; Individual and group service-learning